Credit expansion and social welfare in the European Union - Stanislav Percic (CES Working Papers, 2019)
The aim of this paper is to analyse the impact of the credit expansion process on social welfare through the financial-monetary dimension with a focus on 22 economies from the European Union. In order to achieve this aim, the study seeks, on the one hand, to analyse the short-term dynamics (from one quarter to the other) of the relationships between the total volume of domestic credit to private sector (highlighting thus the credit expansion process) and the GDP per capita (the proxy for social welfare) and, on the other hand, to determine the impact of credit expansion on social welfare on medium and long term using the multiple regression model. The findings revealed that even the correlation between the credit expansion and social welfare is very strong and positive in almost all the analysed countries, the total volume of domestic credit to private sector influences unidirectionally the GDP per capita in only 11 of the 22 states. However, on medium and long term, the credit expansion process has a positive effect on social welfare in all the analysed EU countries.
Keywords: 330; social welfare; credit expansion; financial crisis; GDP